2011 International Topical Meeting on Microwave Photonics Jointly Held With the 2011 Asia-Pacific Microwave Photonics Conferenc 2011
DOI: 10.1109/mwp.2011.6088692
|View full text |Cite
|
Sign up to set email alerts
|

Analog link performance of mode-locked laser diodes in the 60 GHz range

Abstract: In this paper, we present an experimental link performance analysis of mode-locked laser based radio-over fiber systems operating in the millimeter-wave range around 60 GHz. Both directly and externally modulation links are evaluated in terms of maximum output power, link loss, system noise figure and achievable dynamic range. Key parameters for the design and system application of mode-locked laser diodes are identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…From Fig. 2 and computations, it can also be observed that the beat-note RIN mmw is higher than the initial RIN ini by a factor I 2 /I 1 = 6.7 dB because the optical power of DFB 2 is larger , the RIN of less powerful mode (RIN 1 ) in (5) is then increased by a factor I 2 /I 1 compared to RIN 1 in (4) as expected.…”
Section: Rin In [9 Khz -19 Ghz] Frequency Bandsupporting
confidence: 72%
See 2 more Smart Citations
“…From Fig. 2 and computations, it can also be observed that the beat-note RIN mmw is higher than the initial RIN ini by a factor I 2 /I 1 = 6.7 dB because the optical power of DFB 2 is larger , the RIN of less powerful mode (RIN 1 ) in (5) is then increased by a factor I 2 /I 1 compared to RIN 1 in (4) as expected.…”
Section: Rin In [9 Khz -19 Ghz] Frequency Bandsupporting
confidence: 72%
“…2. For verifying (4) and (5), the bias current of the first laser DFB 1 is set to 15 mA (P opt = -2.1 dBm) while the bias current of the second laser DFB 2 is 90 mA (P opt = +3.5 dBm), thus RIN 1 and RIN 2 levels are very different for the first and second laser respectively. The experimental and theoretical results of initial RIN ini and beat-note RIN mmw are given in Fig.…”
Section: Rin In [9 Khz -19 Ghz] Frequency Bandmentioning
confidence: 99%
See 1 more Smart Citation